The Calorie Count of Evaluation - Michael Scriven (The Evaluation Center at Western Michigan University, 2010)
We all know one kind of answer to the question of the value of evaluations; they can help to improve the evaluands, and/or establish accountability for the expenditure that created or supports or buys the evaluands, and/or increase our knowledge about the evaluands' merit, worth, or significance, etc. Those answers are about the useful functions of evaluation; they're like saying that food can help build bone structure and/or muscle mass and/or brain mass; these are all functions that food performs. But there's a more fundamental and more specific level at which we say that a particular food has a certain calorie count, a certain fat content, a certain sugar content, has some iron or peanut oil or salt in it, etc. That level of analysis-a kind of nitty-gritty or component level-is very valuable for the nutritionist and for many consumer concerns. What is the equivalent of this kind of answer for evaluations? Is this a level of analysis we have been overlooking?